One step procedure for screening and diagnosis of gestational diabetes mellitus by diabetes in pregnancy study group of India - L., Dwarakanath; R., Hema K.; P., Hemashree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: In the Indian context, screening for Diabetes is essential in all pregnant women, as the Indian women have an eleven-fold increased risk of developing glucose intolerance during pregnancy. For this, we need a simple procedure which is economical and feasible. Hence this study was undertaken as a screening as it is acceptable, economical and feasible to perform. Aim of this study was to assess the feasibility of one step procedure for screening and diagnosis of Gestational Diabetes Mellitus by Diabetes in Pregnancy Study Group of India (DIPSI).aim of the study was to study the occurrence of Gestational Diabetes mellitus, Tumkur, to assess the sensitivity and specificity of glucose challenge test, to assess the need for universal screening and to study the maternal and perinatal outcomes in patient with Gestational Diabetes Mellitus. Method: Type of study was prospective study. this study included 200 pregnant women attending the antenatal OPD in Sri Siddhartha Medical College, Tumkur. Data collection was in a predesigned proforma. Pregnant women with 24-28 weeks of gestation were given 75 grams of oral glucose load, irrespective of their meal and venous blood sample drawn after 2 hours. If blood glucose value was ≥140mg/dl, the screening was considered as DIPSI positive. These patients underwent OGTT. Results: Incidence of GDM was found to be 3.5% in the patients studied. 40% of cases did not have risk factors, hencethere is a need for universal screening. DIPSI was positive in 10 cases, of which 7 were OGTT positive. Patients were managed with diet and insulin. The maternal and perinatal outcome of pregnancy was good. Conclusion: For universal screening, DIPSI performed irrespective of last meal timing with 75g glucose load is a patient friendly approach. This method recommended by WHO serves both as a one-step screening and diagnostic procedure & is easy to perform besides being economical.